The role of religion in the explanation of the “Russian marriage paradox”: the relational competence hypothesis using the example of spouses who identify themselves as orthodox - Ivan Pavlyutkin; Mariia Goleva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article represents a hypothesis about the interrelation between religion and the "Russian marriage paradox", which consists of simultaneously high levels of marriage and divorce rates as well as a significant proportion of marriages with a short duration. In contrast to the arguments about the "value shifts" and "weak institutions" used today in sociology and demography to explain the transformation of attitudes towards marriage, we propose a hypothesis about the significance of religious ethics - a source of competencies that contribute to the sustainability of married life. Our assumption is that due to the so-called “forced secularization” and detraditionalization of family life in post-Soviet Russia a radical disengagement took place between the normative side of marriage, and the relational side of marriage, which is responsible for manifestations of reciprocity and community in family life. One of the manifestations of this relational ethics, formulated in the social sciences, is associated with the importance of detachment from “Self” in marriage in favor of the “We”, which reflects the Christian ideas of humility, forgiveness, self-sacrifice in the family and promotes marital reciprocity. Studies of recent decades show that the relationship between individual measures of religiosity and family well-being is not linear, but is mediated by the manifestation of virtues in marriage. Based on data from a survey of married Russians who identify themselves as Orthodox (N = 583), we test the assumption that the importance of detachment from “I” in marriage will increase with the rise in the frequency of attendance of religious services and the marriage duration. The theoretical arguments of the hypothesis indicate the significant role of relational competencies responsible for the interconnection between the value of marriage and marriage sustainability. On the one hand, we show that the higher is the duration of marriage and the frequency of attending religious services, the higher is the value of detachment from the “Self”. On the other hand, the relationship between these measures is rather weak. As the conclusion, the explanation for the "Russian marriage paradox" could be related to the "relational poverty" of young people entering into marriage.